2020
DOI: 10.1111/jdi.13269
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing peripheral neuropathy in South‐East Asia: A focus on diabetic neuropathy

Abstract: Burning and stabbing pain in the feet and lower limbs can have a significant impact on the activities of daily living, including walking, climbing stairs and sleeping. Peripheral neuropathy in particular is often misdiagnosed or underdiagnosed because of a lack of awareness amongst both patients and physicians. Furthermore, crude screening tools, such as the 10‐g monofilament, only detect advanced neuropathy and a normal test will lead to false reassurance of those with small fiber mediated painful neuropathy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
0
26
1
Order By: Relevance
“…Despite the introduction of national diabetes pathways in Qatar, the present study confirms an alarmingly high prevalence of undiagnosed DPN in PHC and SHC 2,9 . It highlights the considerable need to educate both patients and physicians on DPN and pDPN 41 . This might explain why up to 25% of patients with diabetes in SHC in Qatar have foot problems 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of national diabetes pathways in Qatar, the present study confirms an alarmingly high prevalence of undiagnosed DPN in PHC and SHC 2,9 . It highlights the considerable need to educate both patients and physicians on DPN and pDPN 41 . This might explain why up to 25% of patients with diabetes in SHC in Qatar have foot problems 16 .…”
Section: Discussionmentioning
confidence: 99%
“…As we aim for a cost-effective and simple DSPN severity classifier, we need data from a screening method, which is simple, inexpensive, accurate, non-invasive, and does not require expensive instruments or tools. Besides increasing patient's awareness and urgency about the seriousness of DSPN, simple diagnosis tools like a 128-Hz tuning fork, monofilament test and temperature sensation test, reflexes of ankle test are required to be provided to the primary healthcare professionals [38]. So, we have selected Michigan Neuropathy Screening Instrumentation (MNSI) [28] as input to train our DSPN severity classifier using the ANFIS algorithm.…”
Section: ) Emg Based Dspn Severity Stratification Using Anfis Modelmentioning
confidence: 99%
“…Diabetic sensorimotor polyneuropathy (DSPN) is the commonest form; it affects approximately 30% of individuals with diabetes and its yearly incidence amounts to approximately 2% 3 . A recent review reported prevalence rates of DSPN in different South-East Asian countries ranging between 33 and 58% among patients with diabetes 4 . A retrospective survey of 1,078 patient records and interviews in primary care clinics in Thailand reported a prevalence of DSPN of 34% among diabetes patients 5 .…”
Section: Epidemiology and Clinical Impact Of Diabetic Neuropathymentioning
confidence: 99%
“…This might be due to a lack of consensus on screening and diagnosis. In most countries, only experts have even simple screening tools, and so many general practitioners do not know how to use them 4 . According to a survey from Thailand, just 45% of patients with diabetes undergo annual foot examinations, which might explain the high frequency of foot ulcers 5,17 .…”
Section: Epidemiology and Clinical Impact Of Diabetic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation